2016
DOI: 10.1038/srep31142
|View full text |Cite
|
Sign up to set email alerts
|

The role of mTOR signalling in the regulation of skeletal muscle mass in a rodent model of resistance exercise

Abstract: Resistance exercise (RE) activates signalling by the mammalian target of rapamycin (mTOR), and it has been suggested that rapamycin-sensitive mTOR signalling controls RE-induced changes in protein synthesis, ribosome biogenesis, autophagy, and the expression of peroxisome proliferator gamma coactivator 1 alpha (PGC-1α). However, direct evidence to support the aforementioned relationships is lacking. Therefore, in this study, we investigated the role of rapamycin-sensitive mTOR in the RE-induced activation of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
179
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(209 citation statements)
references
References 59 publications
15
179
1
2
Order By: Relevance
“…In accordance with this hypothesis, we found that the protein intake that is required to maintain good muscle strength with ageing is increased in the presence of high interleukin‐6 levels . Also, consistent with this hypothesis, previous studies have shown that insulin resistance and diabetes are associated with an accelerated decline in muscle strength, mass, and quality with ageing and also that muscle mass affects insulin sensitivity . Surprisingly, in our metabolomics study presented above, blood leucine and isoleucine levels significantly correlated with BMI but not with insulin.…”
Section: Amino Acid Uptake Mitochondrial Function and Muscle Qualitysupporting
confidence: 90%
“…In accordance with this hypothesis, we found that the protein intake that is required to maintain good muscle strength with ageing is increased in the presence of high interleukin‐6 levels . Also, consistent with this hypothesis, previous studies have shown that insulin resistance and diabetes are associated with an accelerated decline in muscle strength, mass, and quality with ageing and also that muscle mass affects insulin sensitivity . Surprisingly, in our metabolomics study presented above, blood leucine and isoleucine levels significantly correlated with BMI but not with insulin.…”
Section: Amino Acid Uptake Mitochondrial Function and Muscle Qualitysupporting
confidence: 90%
“…Myostatin deactivates the mammalian target of rapamycin (mTOR) resulting in decreased protein synthesis and increased autophagy, at least in part mediated through downstream molecules as p70S6K and 4E‐BP1 . Several physiological factors are triggered by resistance training, but among other, weight training activates protein synthesis trough the above mentioned mTOR pathway . This indicates exercise can counteract hyperammonaemia.…”
Section: Discussionmentioning
confidence: 99%
“…Once mTORC1 is activated, it is believed to activate downstream signalling through, eg, p70S6K and rpS6 and subsequently promote muscle protein translation initiation . Indeed, several studies have shown that mTORC1 signalling is activated following a mechanical stimulus, and moreover, the subsequent increases in protein synthesis and hypertrophy is dependent on mTORC1 signalling . Consequently, mTORC1 signalling is regarded as vital for transducing a mechanical stimulus into biochemical signalling for muscle protein synthesis.…”
Section: Introductionmentioning
confidence: 99%